2014
DOI: 10.1007/s13361-014-0860-9
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Mass Spectrometric Fragmentation on the Bromine Substitution Pattern of Polybrominated Diphenyl Ethers

Abstract: This study investigates the link between the bromine substitution and the mass spectrometric fragmentation of polybrominated diphenyl ethers (PBDEs). The mass spectra of 180 PBDEs were obtained in both electron impact (EI) and electron capture negative ionization (ECNI) modes using a single quadrupole mass spectrometer (MS) as well as EI using a tandem MS (MS/MS). The major ions are M(+), [M-2Br](+), [M-2Br](2+) and [M-nBr-28](+) in EI, and Br(-), [HBr2](-) and [C6BrnO](-) in ECNI. In EI-MS, congeners without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…24 PBDE congeners can also produce doubly charged ions of [M−2Br] 2+ upon EI ionization, particularly for those with no ortho bromine or having 2,3-substitution on one ring and no ortho bromines on the other. 25 The formation of a dibenzofuran-like fragment ion during EI ionization of PBDEs was proposed. 26 In the present study, the doubly charged ion [M] 2+ observed in the EI spectra of halogenated carbazoles may reflect their structural similarity to halogenated dibenzofurans.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 PBDE congeners can also produce doubly charged ions of [M−2Br] 2+ upon EI ionization, particularly for those with no ortho bromine or having 2,3-substitution on one ring and no ortho bromines on the other. 25 The formation of a dibenzofuran-like fragment ion during EI ionization of PBDEs was proposed. 26 In the present study, the doubly charged ion [M] 2+ observed in the EI spectra of halogenated carbazoles may reflect their structural similarity to halogenated dibenzofurans.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the DIUTHAME mass spectrum (Figure a), strong peaks around m / z 486 are predominantly observed and identified as C 6 Br 5 O – by comparing the pattern to the theoretical isotope distribution. It is a representative fragment of DBDE in negative-ion mode. , In the MALDI mass spectrum (Figure b), C 6 Br 5 O – is also observed with no intact DBDE but together with strong peaks of matrix clusters. It is difficult to prevent this interference of matrix cluster ions, regardless of the matrix.…”
Section: Resultsmentioning
confidence: 98%
“…It becomes even more severe when analyzing low concentrations of DBDE as described below. C 6 Br 5 O – ions can also be generated from nona-BDEs (BDE-207 and BDE-208) and octa-BDE (BDE-204) . This absence of discrimination is not detrimental to rapid screening, since these homologs are also comprehensively banned.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations